Beyond self entitlement - U Tun Aung, Maularna Akbar Shah (2019)
We live in the age of entitlement. We have an inflated and a grandiose sense of self, and we may have inadvertently dismissed the need for love, warmth and caring for people other than ourselves. Looking at your current lifestyle, do you see yourself doing something in return to the society that you live in? Is there a possibility for you to not just be a Muslim but lead a responsive lifestyle by guiding others in the community to be well? Draw some inspiration from the speaker as he urges us to go beyond looking at just ourselves and our interests.